Yellow phosphorus tailing-based mine filling material and application thereof
Through the use of raw material compounding and the use of specific excitants, gelled materials containing Aft, C-S-H and C-A-S-H gels were prepared, which solved the problems of low fluidity, high water secretion rate and insufficient strength of mine filling materials in the prior art, and achieved the Efficient solid waste treatment and filling material performance improvement.
Patent Information
- Application Number
- CN202411639485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-21
AI Technical Summary
It is difficult to prepare mine filling materials with high fluidity, low water excretion rate and high strength for the treatment of yellow phosphorus tailings solid waste.
The depolymerization-polycondensation reaction and hydration reaction of raw material compound and specific excitants are carried out to prepare gelling materials containing Aft (ettringite), C-S-H gel and C-A-S-H gel, and the solid waste and excitants are adjusted. Types, adjust the content of alkaline components and sulfate components in the exciter, and improve the density and strength of the material.
It is realized that while treating yellow phosphorus tailings solid waste, it can obtain mine filling materials with high fluidity, low water secretion rate and high strength, and it has the ability to cure soluble F, P and other heavy metal ions.
Smart Images

Figure BDA0005138054770000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mine filling, in particular to a yellow phosphorus tailings-based mine filling material and application thereof. Background Art
[0002] Phosphate tailings are solid wastes generated during the beneficiation of phosphate ore. The production of 1 ton of phosphate concentrate produces about 0.44 tons of phosphate tailings, the production of 1 ton of phosphoric acid produces about 4 to 5 tons of phosphogypsum, and the production of 1 ton of yellow phosphorus produces 8 to 10 tons of yellow phosphorus slag. Phosphate tailings, phosphogypsum, and yellow phosphorus slag contain soluble elements such as F and P. The accumulation process not only wastes land resources, but also pollutes soil and water resources and harms the ecological environment. At present, the main ways to use phosphate tailings, phosphogypsum, and yellow phosphorus slag are to produce building materials, fertilizers, and filling materials.
[0003] In order to improve the utilization rate of waste materials such as phosphate tailings, relevant technologies use them as raw materials for filling materials, which can not only consume a large amount of phosphate solid waste, improve the comprehensive utilization rate of phosphate solid waste, avoid occupying land resources, but also reduce pollution to the environment and reduce the cost of solid waste management for enterprises. However, the filling materials prepared by relevant technologies are not suitable as mine filling materials. The reason is that the fluidity of the obtained filler is low, the water seepage rate is high, and the strength still needs to be improved, so the phosphate tailings after solid waste treatment are not widely used.
[0004] Therefore, it is necessary to provide a solid waste treatment method for phosphate tailings to obtain a mine filling material with high fluidity, low water seepage rate and high strength. Summary of the invention
[0005] In view of this, the present application provides a yellow phosphorus tailings-based mine filling material and its application, which is used to solve the problem of how to obtain a mine filling material with high fluidity, low water seepage rate and high strength while treating yellow phosphorus tailings solid waste.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0007] In the first aspect, the present application provides a yellow phosphorus tailings-based mine filling material, which includes aggregate and cementitious material; the cementitious material includes the following components in mass fractions: 5-20 parts of red mud, 20-40 parts of yellow phosphorus slag, 10-30 parts of slag, 5-10 parts of fly ash, 5-10 parts of compound activator, 1-3 parts of early strength agent, 2-5 parts of water retention agent; wherein the compound activator includes the following components in mass fractions: 10-20 parts of sodium metasilicate, 30-40 parts of gypsum powder, 20-30 parts of sodium sulfate, 5-10 parts of carbide slag, and 5-10 parts of silica fume.
[0008] Preferably, the water retaining agent includes one or more of sodium carbonate, alkali metal sulfate, and hydroxypropyl methylcellulose ether.
[0009] Preferably, the early strength agent includes one or more of sodium aluminate, calcium formate and aluminum sulfate.
[0010] Preferably, the aggregate comprises phosphate tailings and phosphogypsum in a mass ratio of 2-4:1.
[0011] Preferably, the mass ratio of aggregate to cementitious material is 4-6:1.
[0012] Preferably, the particle size of red mud is 45≤D90≤70μm, and the particle size of yellow phosphorus slag, slag and fly ash is 5≤D90≤35μm.
[0013] Preferably, the particle size of gypsum powder and carbide slag is 10≤D90≤35μm, and the particle size of silica fume is 1≤D90≤2μm.
[0014] Preferably, the gypsum powder includes one or more of α-gypsum and β-gypsum.
[0015] In a second aspect, the present application provides an application of a yellow phosphorus tailings-based mine filling material. The yellow phosphorus tailings-based mine filling material is mixed with water to form a slurry, which is then transported to a mine for solidification and filling.
[0016] Preferably, the slurry concentration is 0.70-0.75.
[0017] The beneficial effects of the present application are as follows: the present application obtains a cementitious material containing Aft (ettringite), CSH gel (hydrated calcium silicate gel) and CASH gel (hydrated calcium aluminosilicate gel) by compounding raw materials and using a specific stimulant for depolymerization-polycondensation reaction, and by compounding raw materials and using a specific stimulant for depolymerization-polycondensation reaction and hydration reaction, and increases the amount of Aft (ettringite), CSH gel and CASH gel by adjusting the types of solid waste and stimulant and adjusting the contents of alkaline components and sulfate components in the stimulant, while ensuring the formation of a composite gel when the cementitious material fills the gaps between aggregates, further increasing the density and strength of the filling material, and ultimately obtaining a mine filling material with high fluidity, low water seepage rate, high strength, and strong ability to solidify soluble F, P and other heavy metal ions while treating yellow phosphorus tailings solid waste. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The present application provides a yellow phosphorus tailings-based mine filling material, which includes aggregate and cementitious material; the cementitious material includes the following components in mass fractions: 5-20 parts of red mud, 20-40 parts of yellow phosphorus slag, 10-30 parts of slag, 5-10 parts of fly ash, 5-10 parts of compound activator, 1-3 parts of early strength agent, 2-5 parts of water retaining agent; wherein the compound activator includes the following components in mass fractions: 10-20 parts of sodium metasilicate, 30-40 parts of gypsum powder, 20-30 parts of sodium sulfate, 5-10 parts of carbide slag, and 5-10 parts of silica fume.
[0020] In the present application, a cementitious material containing Aft (ettringite), CSH gel (hydrated calcium silicate gel) and CASH gel (hydrated calcium aluminosilicate gel) is obtained by compounding raw materials and carrying out depolymerization-polycondensation reaction and hydration reaction with a specific activator, and the content of alkaline components and sulfate components in the activator is adjusted by adjusting the types of solid waste and activators, thereby increasing the amount of Aft (ettringite), CSH gel and CASH gel obtained, and ensuring the formation of a composite gel when the cementitious material fills the gaps between aggregates, thereby further increasing the density and strength of the filling material, and finally obtaining a mine filling material with high fluidity, low water seepage rate, high strength, and strong ability to solidify soluble F, P and other heavy metal ions while treating yellow phosphorus tailings solid waste.
[0021] Specifically, red mud and fly ash contain a large amount of aluminosilicate. Using sodium metasilicate (Na2SiO3) and carbide slag as activator components can adjust the alkalinity of the reaction process. In an alkaline environment, in the presence of OH - [SiO4] can be dissolved under the action of 4- and [AlO4] 5- , promoting the formation of CASH gel; slag and yellow phosphorus slag are highly active and have high Ca content, and have potential volcanic ash activity. 4- and [AlO4] 5- Ca is also dissolved 2+ , some of them can generate CSH gel through hydration reaction, and can also generate CASH gel under alkali excitation conditions; in the compound activator, silica fume and sodium metasilicate (Na2SiO3) have a synergistic effect to accelerate the hydration reaction of the above substances, and the silica fume particles are small, and the unreacted silica fume can also fill the gaps in the filling material, making the filling material structure more compact. The synergistic effect of red mud and sodium metasilicate can utilize the high alkalinity of red mud to increase the pH value in the reaction system, accelerate the rate of alkali excitation reaction, and improve the cementing properties of the material. On the other hand, the sodium sulfate, gypsum in the compound activator and the phosphogypsum in the aggregate can provide SO4 2- , Ca 2+ With [AlO4] 5- and OH- The formation of calcium sulfide (AFt) improves the early strength. Since the main component of calcium carbide slag is Ca(OH)2, it can also generate CaSO4 and OH by reacting with sulfate. - , the generated OH - It can also promote the rate of alkali-induced reaction and further reduce the water seepage rate under the action of water retaining agent. Under the action of alkali excitation, sulfate and hydration reaction, Aft (ettringite), CSH gel and CASH gel are generated in the raw materials. The two gels and ettringite form a dense structure, which can stabilize and solidify heavy metal ions in it, free PO4 in phosphogypsum and yellow phosphorus slag 3- Also with Ca 2+ OH - The reaction generates insoluble phosphates, thus achieving the solidification of soluble P.
[0022] In some embodiments, the water retaining agent includes one or more of sodium carbonate, alkali metal sulfate, and hydroxypropyl methylcellulose ether.
[0023] Among them, sodium carbonate mixed with sodium metasilicate as an activator can adjust the coagulation time and obtain an ideal coagulation time, thereby reducing the water bleeding rate; alkali metal sulfate can increase the liquid phase ion strength, shorten the induction period, promote the hydration process of the raw materials, and promote the formation of calcium aluminate, thereby improving the early strength; the hydroxyl group of hydroxypropyl methylcellulose ether (HPMC) can combine with water molecules to form hydrogen bonds, thereby achieving the effect of adsorbing water molecules, and the methyl group can form a protective film on the molecular surface to prevent the escape of water molecules.
[0024] In some embodiments, the early strength agent includes one or more of sodium aluminate, calcium formate, and aluminum sulfate.
[0025] In some embodiments, the aggregate includes phosphate tailings and phosphogypsum in a mass ratio of 2-4:1; the water content of the phosphate tailings and phosphogypsum in the aggregate is ≤10%.
[0026] In some embodiments, the mass ratio of aggregate to cementitious material is 4-6:1.
[0027] In some embodiments, the particle size of red mud is 45≤D90≤70μm, and the particle size of yellow phosphorus slag, slag, and fly ash is 5≤D90≤35μm. Since red mud has a large specific surface area, a small particle size of red mud will lead to a high water demand, which is not conducive to the hydration reaction; slag and yellow phosphorus slag are active ingredients, and the smaller the particle size, the larger the specific surface area, and the more sufficient the hydration reaction is, which is conducive to the improvement of mechanical properties.
[0028] In some embodiments, the particle size of gypsum powder and carbide slag is 10≤D90≤35μm, the particle size of silica ash is 1≤D90≤2μm, and the SiO2 content in the silica ash is ≥94%; the larger particle size of gypsum and carbide slag will affect the activity and is not conducive to the improvement of mechanical properties. The silica ash has finer particles and higher activity, which can improve the interface bonding between the filler and the matrix.
[0029] In some embodiments, the gypsum powder includes one or more of α-gypsum and β-gypsum.
[0030] A method for preparing a yellow phosphorus tailings-based mine filling material comprises the following steps:
[0031] Drying: Dry red mud, yellow phosphorus slag, slag, fly ash and carbide slag in an oven at 110℃ for 24 hours to ensure that the moisture content is ≤1%; dry gypsum powder in an oven at 40℃ to ensure that the moisture content is ≤1%; dry phosphorus tailings and phosphogypsum in an oven at 110℃ to ensure that the moisture content is ≤10%.
[0032] Ball milling: ball mill the raw materials of cementitious materials and aggregates separately;
[0033] Mixing: Evenly mix the processed cementitious material and aggregate raw material components to obtain powder, that is, the yellow phosphorus tailings-based mine filling material.
[0034] The present application provides an application of a yellow phosphorus tailings-based mine filling material. The yellow phosphorus tailings-based mine filling material is mixed with water to form a slurry, which is then transported to a mine for solidification and filling.
[0035] In some embodiments, the slurry concentration is 0.70-0.75. When the concentration is lower than this, the water permeability is too high, and when the concentration is higher than this, the slump is low, which is not conducive to the preparation and application of the filling material.
[0036] The present solution is further described below through specific embodiments.
[0037] Example 1
[0038] A yellow phosphorus tailings-based mine filling material has a slurry concentration of 0.75 and comprises aggregates and cementitious materials in a mass ratio of 5:1; the cementitious materials comprise the following components in mass fractions: 10 parts of red mud, 30 parts of yellow phosphorus slag, 20 parts of slag, 8 parts of fly ash, 10 parts of compound activator, 2 parts of aluminum sulfate, 4 parts of sodium carbonate, and 0.01 parts of hydroxypropyl methylcellulose; the aggregate comprises phosphorus tailings and phosphogypsum in a mass ratio of 3:1; wherein the compound activator comprises the following components in mass fractions: 20 parts of sodium metasilicate, 40 parts of beta gypsum, 20 parts of sodium sulfate, 15 parts of carbide slag, and 5 parts of silica fume. The particle size of red mud is D90=50μm, the D90 particle sizes of yellow phosphorus slag, slag and fly ash are 10μm, 20μm and 30μm respectively; the D90 particle sizes of gypsum powder and carbide slag are 20μm and 35μm respectively, and the particle size of silica fume is D90=2μm.
[0039] Example 2
[0040] A yellow phosphorus tailings-based mine filling material, comprising aggregate and cementitious material in a mass ratio of 4:1; the cementitious material comprises the following components in mass fractions: 5 parts of red mud, 40 parts of yellow phosphorus slag, 30 parts of slag, 5 parts of fly ash, 5 parts of compound activator, 1 part of aluminum sulfate, 2 parts of sodium carbonate, and 0.01 parts of hydroxypropyl methylcellulose; the aggregate comprises phosphorus tailings and phosphogypsum in a mass ratio of 2:1; wherein the compound activator comprises the following components in mass fractions: 10 parts of sodium metasilicate, 30 parts of beta gypsum, 30 parts of sodium sulfate, 10 parts of carbide slag, and 10 parts of silica fume. The particle size of red mud is D90=50μm, the particle sizes of yellow phosphorus slag, slag, and fly ash are 5μm, 25μm, and 35μm, respectively; the particle sizes of gypsum powder and carbide slag are 20μm and 35μm, respectively, and the particle size of silica fume is D90=1μm.
[0041] Example 3
[0042] A yellow phosphorus tailings-based mine filling material comprises aggregate and cementitious material in a mass ratio of 6:1; the cementitious material comprises the following components in mass fractions: 20 parts of red mud, 20 parts of yellow phosphorus slag, 10 parts of slag, 10 parts of fly ash, 10 parts of compound activator, 3 parts of aluminum sulfate, 5 parts of sodium carbonate, and 0.01 parts of hydroxypropyl methylcellulose; the aggregate comprises phosphorus tailings and phosphogypsum in a mass ratio of 2:1; wherein the compound activator comprises the following components in mass fractions: 15 parts of sodium metasilicate, 20 parts of beta gypsum, 20 parts of sodium sulfate, 10 parts of carbide slag, and 10 parts of silica fume. The particle size of red mud is D90=45μm, the D90 particle sizes of yellow phosphorus slag, slag and fly ash are 10μm, 15μm and 35μm respectively; the D90 particle sizes of gypsum powder and carbide slag are 15μm and 25μm respectively, and the particle size of silica fume is D90=1μm.
[0043] Comparative Example 1
[0044] A yellow phosphorus tailings-based mine filling material, the other contents of which are the same as those of Example 1, except that sodium metasilicate is replaced by beta gypsum.
[0045] Comparative Example 2
[0046] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that no water retaining agent is included.
[0047] Comparative Example 3
[0048] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that red mud and fly ash are not included.
[0049] Comparative Example 4
[0050] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that slag and yellow phosphorus slag are not included.
[0051] Comparative Example 5
[0052] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that silica fume and sodium metasilicate are not included.
[0053] Comparative Example 6
[0054] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that sodium metasilicate is not included.
[0055] Comparative Example 7
[0056] A yellow phosphorus tailings-based mine filling material, other contents of which are the same as those of Example 1, except that sodium sulfate, gypsum and phosphogypsum are not included.
[0057] Test and Evaluation
[0058] The yellow phosphorus tailings-based mine filling materials of the embodiment and the comparative example were tested, wherein the water bleeding rate and slump test methods were carried out with reference to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" GB / T 50080-2016, and the uniaxial compressive strength and expansion of the test block were carried out with reference to the "Technical Standard for Metal and Non-metal Mine Filling Engineering" GB / T 51450-2022. The experimental results are shown in Table 1.
[0059] Table 1 Test results
[0060]
[0061] From the above data, it can be seen that the yellow phosphorus tailings-based mine filling material obtained by compounding raw materials and specific activators in this application has low water seepage rate, high uniaxial compressive strength and expansion, and at the same time, solid waste treatment of yellow phosphorus tailings, yellow phosphorus slag, phosphogypsum, red mud, etc. is carried out.
[0062] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A yellow phosphorus tailings-based mine filling material, characterized in that: It includes aggregate and cementitious material; the cementitious material includes the following components in mass proportions: 5-20 parts of red mud, 20-40 parts of yellow phosphorus slag, 10-30 parts of slag, 5-10 parts of fly ash, 5-10 parts of compound activator, 1-3 parts of early strength agent, 2-5 parts of water retaining agent; wherein the compound activator includes the following components in mass proportions: 10-20 parts of sodium metasilicate, 30-40 parts of gypsum powder, 20-30 parts of sodium sulfate, 5-10 parts of carbide slag, and 5-10 parts of silica fume.
2. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The water retaining agent includes one or more of sodium carbonate, alkali metal sulfate and hydroxypropyl methylcellulose ether.
3. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The early strength agent includes one or more of sodium aluminate, calcium formate and aluminum sulfate.
4. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The aggregate comprises phosphate tailings and phosphogypsum in a mass ratio of 2-4:
1.
5. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The mass ratio of the aggregate to the cementitious material is 4-6:
1.
6. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The particle size of the red mud is 45≤D90≤70μm, and the particle size of the yellow phosphorus slag, slag and fly ash is 5≤D90≤35μm.
7. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The particle size of the gypsum powder and carbide slag is 10≤D90≤35μm, and the particle size of the silica fume is 1≤D90≤2μm.
8. The yellow phosphorus tailings-based mine filling material according to claim 1, characterized in that: The gypsum powder includes one or more of α-gypsum and β-gypsum.
9. An application of the yellow phosphorus tailings-based mine filling material according to any one of claims 1 to 8, characterized in that: The yellow phosphorus tailings-based mine filling material is mixed with water to form a slurry, which is then transported to the mine for solidification and filling.
10. The use according to claim 9, characterized in that: The slurry concentration is 0.70-0.75.
Citation Information
Cited By
Phosphorus tailing filling material and application thereof
CN119841592A
Yellow phosphorus slag-phosphogypsum-yellow phosphorus tailing mortar-based filling material as well as preparation method and application thereof
CN120774685A
Filling gel material and preparation method thereof
CN121850552A
A filled gel material and a method for its production
CN121850552B
Method for solidifying water-based drilling mud by alkali-activated copper slag-based cementing material based on pre-reaction strategy
CN122167090A